2019
DOI: 10.1155/2019/2927061
|View full text |Cite
|
Sign up to set email alerts
|

Specific Autoantibodies and Clinical Phenotypes Correlate with the Aberrant Expression of Immune-Related MicroRNAs in Dermatomyositis

Abstract: Aims. The serum concentrations of miRNAs, miR-23a-3p, miR-23b-3p, miR-146a-5p, miR-146b-5p, and miR-150-5p, were shown to be associated with the immune and inflammatory progressions. We assessed the expressions of these five miRNAs in association with clinical phenotypes and myositis-specific autoantibody-defined subgroups of dermatomyositis (DM). Methods. The present study included 49 patients with DM and 30 healthy controls. The serum concentrations of miR-23a-3p, miR-23b-3p, miR-146a-5p, miR-146b-5p, and mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 36 publications
1
11
1
Order By: Relevance
“…Bars indicate the mean ± SEM patients. The relation between serum level of this micro-RNA and antibody production was reported previously (Ye et al 2019). Significantly higher levels of diverse immunoglobulins classes were present in blood of miR-150 knockout mice (Xiao et al 2007).…”
Section: Discussionsupporting
confidence: 69%
“…Bars indicate the mean ± SEM patients. The relation between serum level of this micro-RNA and antibody production was reported previously (Ye et al 2019). Significantly higher levels of diverse immunoglobulins classes were present in blood of miR-150 knockout mice (Xiao et al 2007).…”
Section: Discussionsupporting
confidence: 69%
“…MiRNAs have regulatory effects on Treg/Th17 balance in several autoimmune diseases [ 35 ]. The serum concentration of miR-23b-3p is associated with the immune and inflammatory progressions [ 36 ]. In our study, we found upregulated Th17 (IL-17) and downregulated Treg cell marker (Foxp3) in the model mice, suggesting that Treg/Th17 imbalance might also occur to obesity-induced IR mice.…”
Section: Discussionmentioning
confidence: 99%
“…Invitro human and mouse models demonstrated that TNF inhibited the expression of these miRNAs and blocked the differentiation of human and mouse myoblasts into myocytes (46). Finally, a relationship between miRNA expression and autoantibody status has been reported, specifically between miR-96-5p upregulation and anti-Jo-1 (44), and miR-150-5p downregulation and anti-MDA5 and anti-nuclear matrix protein-2 (NXP2) (51).…”
Section: Role In Understanding Pathogenesismentioning
confidence: 97%